1997
DOI: 10.1016/s0378-4371(97)00401-9
|View full text |Cite
|
Sign up to set email alerts
|

Price variations in a stock market with many agents

Abstract: Large variations in stock prices happen with sufficient frequency to raise doubts about existing models, which all fail to account for non-Gaussian statistics. We construct simple models of a stock market, and argue that the large variations may be due to a crowd effect, where agents imitate each other's behavior. The variations over different time scales can be related to each other in a systematic way, similar to the Levy stable distribution proposed by Mandelbrot to describe real market indices.In the simpl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
306
2
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 349 publications
(316 citation statements)
references
References 26 publications
5
306
2
3
Order By: Relevance
“…It is shown that such speculative actions make demand and supply balance automatically on average by changing the market price, resembling a kind of self organized criticality. Fig.5 is in total agreement with that: Contrary to [3] we do not need to impose that the number of the shares has to be half of the number of traders in order to get a balance between demand and supply. The three circles in the upper panel indicate the most extreme events taking place in the price evolution: There is a corresponding movement in the book and a peak in the volumes.…”
Section: Parameters' Analysissupporting
confidence: 67%
See 3 more Smart Citations
“…It is shown that such speculative actions make demand and supply balance automatically on average by changing the market price, resembling a kind of self organized criticality. Fig.5 is in total agreement with that: Contrary to [3] we do not need to impose that the number of the shares has to be half of the number of traders in order to get a balance between demand and supply. The three circles in the upper panel indicate the most extreme events taking place in the price evolution: There is a corresponding movement in the book and a peak in the volumes.…”
Section: Parameters' Analysissupporting
confidence: 67%
“…This represents, on our opinion, a realistic upper limit for the market price, since nobody would buy anything if they cannot afford it (maybe the reality is a little bit different; traders stop buying shares when the price is too high not because they do not have money, but because they believe that the price is too far away from a fair 3) Just to give some colors to these numbers, we can imagine the following situation, not too far away from the reality in a big european country. Suppose that 10 million of traders are interested in trading a given new stock and they would like to invest, on average, 3000 EUROs.…”
Section: Parameters' Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Others have proposed artificial markets populated with heterogeneous agents characterised by simple trading rules [4][5][6][7][8][9][10][11]. These lend themselves better to analytical modelling while still retaining the ability to capture fundamental features of market behaviour.…”
Section: Introductionmentioning
confidence: 99%